Characteristics, treatment and outcomes of 589 melanoma patients documented by 27 general practitioners on the Skin Cancer Audit Research Database. (19th April 2022) - Hay, Jeremy; Keir, Jeff; Jimenez Balcells, Clara; Rosendahl, Nikita; Coetzer‐Botha, Martelle; Wilson, Tobias; Clark, Simon; Baade, Astrid; Becker, Cath; Bookallil, Luke; Clifopoulos, Chris; Dicker, Tony; et al.
ABSTRACT: Background and objective: General practitioners manage more melanomas than dermatologists or surgeons in Australia. Previously undescribed, the management and outcomes of melanoma patients treated by multiple Australasian general practitioners are examined. Methods: The characteristics, management and outcomes of 589 melanoma patients, managed by 27 Australasian general practitioners and documented on the Skin Cancer Audit Research Database (SCARD), were analysed. Results: Most patients (58.9%) were males with mean age at diagnosis of 62.7 years (range 18–96), and most melanomas were in situ or thin‐invasive. Patients aged under 40 years had fewer melanomas, but a higher proportion (the majority) were invasive, compared with older patients ( P < 0.0001). Most (55.9%) melanomas were diagnosed following elliptical excision biopsy, the rate of unintended involved margins being eightfold higher for shave biopsies. Wide re‐excision was performed by the treating general practitioner for most (74.9%) melanomas, with thick melanomas preferentially referred to surgeons. The average Breslow thickness of invasive melanomas re‐excised by general practitioners was 0.67 mm compared with 1.99 mm for those referred to other specialists ( P < 0.0001). Of 205 patients with invasive melanoma, 14 progressed to metastatic disease, 50% of these being associated with nodular melanoma. Nine patients progressed to melanoma‐specific death. The 5‐year survival rate for patients with invasive melanoma was 95.2% (95% CI: 91.2–98.5%). Conclusions: Diagnostic and therapeutic management of a series of melanoma patients by Australasian general practitioners were closely aligned with current guidelines and 5‐year survival with respect to invasive melanoma was at least as favourable as national population‐based metrics.